2011
DOI: 10.1002/hep.24099
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of the Fibroblast Growth Factor 8 Subfamily in Human Hepatocellular Carcinoma for Cell Survival and Neoangiogenesis Δσ

Abstract: Fibroblast growth factors (FGFs) and their high-affinity receptors [fibroblast growth factor receptors (FGFRs)] contribute to autocrine and paracrine growth stimulation in several nonliver cancer entities. Here we report that at least one member of the FGF8 subfamily (FGF8, FGF17, and FGF18) was up-regulated in 59% of 34 human hepatocellular carcinoma (HCC) samples that we investigated. The levels of the corresponding receptors (FGFR2, FGFR3, and FGFR4) were also elevated in the great majority of the HCC cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(137 citation statements)
references
References 31 publications
7
124
1
2
Order By: Relevance
“…52). For example, signaling of FGF and Wnt is implicated in HCC development (53)(54)(55), and Wnt signaling regulates hepatoblasts and liver CSC self-renewal (18,(56)(57)(58)(59)(60). Recent application of massive parallel sequencing technologies have consistently confirmed previous findings that somatic mutations of genes in the Wnt/β-catenin signaling pathways, such as axin and β-catenin, are common HCC events (61)(62)(63).…”
Section: Shared Features Of Liver Development and Liver Cancer Develomentioning
confidence: 69%
“…52). For example, signaling of FGF and Wnt is implicated in HCC development (53)(54)(55), and Wnt signaling regulates hepatoblasts and liver CSC self-renewal (18,(56)(57)(58)(59)(60). Recent application of massive parallel sequencing technologies have consistently confirmed previous findings that somatic mutations of genes in the Wnt/β-catenin signaling pathways, such as axin and β-catenin, are common HCC events (61)(62)(63).…”
Section: Shared Features Of Liver Development and Liver Cancer Develomentioning
confidence: 69%
“…In vitro studies have shown that FGF5 overexpression has been associated with a number of tumor cell lines (lung, esophagus, melanoma, colon, and prostate; ref. 23), and in hepatocellular carcinomas (HCC), the upregulation of FGF2, 8, 17, and 18 initiates autocrine growth stimulation, cell survival, and neoangiogenesis (24)(25)(26)(27). Further, HCC has been found to develop in transgenic mice overexpressing the hormonal FGF19 (28), and FGF19 is found on an amplicon on chromosome 11q that also invariably contains the adjacent FGF3, FGF4, and Cyclin D1 (CCND1) genes.…”
Section: Autocrine and Paracrine Signalingmentioning
confidence: 99%
“…FGFR2 is the product of the Bek oncogene expression product and a transmembrane tyrosine kinase receptor with a high affinity for a variety of FGFs (8). Studies have demonstrated (13) that ERCC1 in HCC cells is the downstream target of MEK/ERK and PI3K.…”
Section: Discussionmentioning
confidence: 99%